Representasi Upaya Perempuan Dalam Memperjuangkan Hak Atas Tubuh - Fairuz Rahmawati; Chatarina Heny Dwi Surwati (Jurnal Komunikasi Massa, 2024)
Since the covid-19 pandemic, the number of online streaming viewers in Indonesia has increased. The Indonesian film industry has also begun to launch films that challenge gender stereotypes and traditional beauty standards, for example the web series “Induk Gajah”. This research aims to find out how women's efforts in struggling for body rights are represented in the web series “Induk Gajah”. The use of Sara Mills' critical discourse analysis is carried out to observe the position of the subject, object and reader in the narrative to understand how the value of women's efforts in struggling for body rights. The results of this study found that the web series Induk gajah represents how the main character, Ira, tries to take control of her body and maintain her confidence although she faces pressure from her family and friends. In this web series, Mamak Uli and her friends act as subjects who push the beauty standards and Ira acts as an object. Ira also becomes the subject of the web series when she tries to resist the treatment of Mamak Uli and her friends.This web series emphasizes the importance of resistance to patriarchal norms to get freedom and control over their own bodies.